KCNQ2 Encephalopathy Showing a Distinct Ictal Amplitude-Integrated Electroencephalographic Pattern - Naeun Kwak; Yun Jeong Lee; Dongsub Kim; Su-Kyeong Hwang; Soonhak Kwon; Eun Joo Lee (Korean Society of Neonatology, 2020)
KCNQ2 mutations induce a neonatal-onset epileptic encephalopathy of widely varying severity, ranging from benign familial neonatal epilepsy to severe refractory epileptic encephalopathy. Refractory seizures with KCNQ2 mutations have a positive response to sodium-channel blockers. Recently, a distinctive ictal pattern has been reported during amplitude-integrated electroencephalographic (aEEG) monitoring in infants with KCNQ2 encephalopathy. Herein, we describe a case of KCNQ2 encephalopathy with this distinctive ictal aEEG pattern, which was confirmed using conventional electroencephalography (EEG). A 3-day-old female infant presented with neonatal seizures accompanied by cyanosis and desaturation. Her seizure semiology was tonic and focal clonic. Her ictal aEEG demonstrated a sudden rise in amplitude followed by a suppressed background pattern. This pattern was also confirmed on conventional EEG. Her seizures were refractory despite the administration of multiple conventional antiepileptic drugs. Finally, c.794C>T; p. (Ala265Val) mutation was observed in the KCNQ2 gene on genetic testing, and she was diagnosed with KCNQ2 encephalopathy. Identifying this distinctive ictal pattern on aEEG monitoring facilitates the early detection of KCNQ2 encephalopathy and timely targeted treatment in patients with refractory seizures.